2011
DOI: 10.1111/j.1758-5872.2011.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Korean psychiatric residents

Abstract: Introduction: This study investigated the relationship between empathy and grades, marital status and personality in psychiatric residents. Methods: We sent a questionnaire package to 592 psychiatric residents in 82 psychiatric residency training hospitals. The questionnaire package collected socio-demographic data, and included the Jefferson Scale of Empathy, HP-version, Korean edition (JSE-HP-K), and Temperament and Character Inventory (TCI). Results: Fourth-year residents had significantly higher scores on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
12
0
1
Order By: Relevance
“…Like the studies by Lee et al [10] and Colliver et al [13], this study found no negative effect of clinical experiences on empathy. Hong et al [18] showed empathy in Korean psychiatric residents was higher in senior residents. Cultural or educational differences between the East and the West could be assumed to be the reason for these conflicting results, and the positive factors for improving empathy needed to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Like the studies by Lee et al [10] and Colliver et al [13], this study found no negative effect of clinical experiences on empathy. Hong et al [18] showed empathy in Korean psychiatric residents was higher in senior residents. Cultural or educational differences between the East and the West could be assumed to be the reason for these conflicting results, and the positive factors for improving empathy needed to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the remaining 305 articles were examined for goodness of fit with the study criteria. This process resulted in the exclusion of 196 of these publications, leaving 109 articles . Subsequently, the following information was extracted from each remaining article: the definition of empathy (if present), and whether the definition incorporated thinking, feeling, acting or more than one of these components.…”
Section: Methodsmentioning
confidence: 99%
“…19 Another study 20 22 In a study at the Cleveland Clinic, 23 statistically significant associations were observed between physicians' JSE scores and standardized measures of patients' communication experiences with their physicians. Also, studies have found that medical students' scores on the JSE are associated with personal qualities that are conducive to relationship building; these qualities include empathetic concern and perspectivetaking 24,25 ; warmth, dutifulness, and compassion 8 ; sociability 26 ; agreeableness; openness to experience; conscientiousness and extraversion 27 ; emotional intelligence [28][29][30] ; cooperativeness 31 ; desirable professional behavior 32 ; positive attitudes toward patientcentered care and orientation toward integrative patient care in osteopathic medical students 33 ; positive social influence 34 ; humanistic excellence by peer nomination 35 ; personal accomplishment 36 ; and orientation toward teamwork and interprofessional collaboration in allopathic 37 and osteopathic medical students. 33,38 Conversely, JSE scores were negatively correlated with personal qualities that are detrimental to relationship building, including aggression-hostility, 26,39 indicators of burnout such as depersonalization and emotional exhaustion, 36,40,41 and neuroticism.…”
Section: Researchers In the United States And Abroad Havementioning
confidence: 99%
“…7( pp276-286) Stability of scores over time indicated by test-retest reliability (0.60-0.69) has been reported in physicians 10 and in osteopathic medical students who participated in POMEE (Hojat et al, unpublished data, 2019). These studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] provide strong evidence of the validity and reliability of the JSE. The JSE has been translated into 56 languages and is used in more than 85 countries.…”
Section: Internal Consistency Reliability (Determined Bymentioning
confidence: 99%